Radial forearm flap plus Flexor Carpi Radialis tendon in Achilles tendon reconstruction: Surgical technique, functional results, and gait analysis. Issue 8 (2nd September 2015) - Innocenti, Marco; Tani, Massimiliano; Carulli, Christian; Ghezzi, Serena; Raspanti, Andrea; Menichini, Giulio
Abstract : Background: Wound dehiscence, infection, and necrosis of tendon and overlying skin are severe complications after open repairs of Achilles tendon. A simultaneous reconstruction should be provided in a single stage operation. We evaluated the outcomes of one of the possible options: the radial forearm free flap with Flexor Carpi Radialis (FCR) tendon. Methods: Between 2006 and 2014, six patients affected by infection and necrosis after Achilles tendon open repair underwent multi‐tissutal reconstruction by a composite radial forearm free flap including a vascularized FCR tendon. The mean skin and tendon defect was respectively 9.8 cm × 4.7 cm and 6.5 cm. After reconstruction, patients underwent clinical examination, including the Achilles Tendon Total Rupture Score (ATRS) questionnaire, DASH score, MRI study, and a computer‐assisted gait analysis. Results: All flaps survived and no complications were recorded. Full weightbearing was allowed within 2 months after surgery. The mean follow‐up was 36.2 months (range 12–96). MRI showed an optimal reconstruction of the tendon. Range of motion was minimally reduced if compared to the contralateral side. Gait analysis showed the recovery of a nearly symmetrical stance phase, time to heel off, and step length of the gate. ATRS and DASH score improved to a mean value of 85.2 (range 83–88) and 8.0 (range 3–15) respectively. Conclusions: This procedure provided an anatomical reconstruction of the Achilles tendon and skin achieving good and objective functional results; donor site morbidity was limited to the sacrifice of the radial artery, which, in our opinion, is a minor drawback if compared to the quality of the results. © 2015 Wiley Periodicals, Inc. Microsurgery 35:608–614, 2015.